Clinical Characteristics and Pattern of Substance Use among Treatment Seeking Adolescents in North India Exploring the Rural-urban Differences - Sunila Rathee; Jagriti Yadav; Vinay Kumar; Ritvik Gupta; Rajiv Gupta; Sidharth Arya (Journal of Mental Health and Human Behaviour)
Background: Adolescent substance use is a pressing issue that requires urgent attention. We analyzed the data for sociodemographic profile, clinical characteristics, and pattern of substance use among adolescents in a tertiary care hospital in North India with a specific emphasis on the differences in substance use in the rural and urban adolescent population. Materials and Methods: A 5-year outpatient record review was done using a preformatted intake sheet for adolescent substance users between the age of 10 and 19 years. Results: A total of 446 adolescents were registered with half (55.8%) of the adolescents belonging to urban backgrounds, whereas 44.2% were from rural background. Most of the adolescents were formally educated till the 10th standard from urban as well as from rural background and had never been employed. The mean age of onset of substance use was 14.78 ± 1.73 years. The earliest age of onset was for tobacco (11.94 years) followed by Cannabis (14.81), alcohol (15.98), and opioids (16.37). However, the most common substance for presentation to the outpatient services was opioid (68.8%) followed by alcohol (14.1%) and cannabis (11.6%). The most common reason for initiation of substance use was experimentation among rural adolescents (21.3%, n = 95), whereas peer influence was the most common reason among urban adolescents (30.0%, n = 134). The most common route of administration of opioids was chasing (57%) followed by the intravenous route (29.3%). Forty-one percent of intravenous users had a history of sharing needles. The use of cannabis and intravenous opioids among adolescents was significantly associated with urban background (P < 0.05). Conclusion: The study reflects the need to increase awareness regarding the consequences of substance misuse among adolescents in both rural and urban areas. The focus areas are educating adolescents about the adverse effects of experimentation, peer influence, legal consequences, high-risk behaviors, and importance of early treatment seeking in substance use.